Fabrication of FeCo/Multidimensional Carbon-Based Nanocomposites as Excellent Cathodic Catalysts of Zn-Air Battery. Issue 11 (1st November 2022) - Fang, Can; Yi, Qingfeng; Chen, Aling; Wang, Yuebing; Wang, Yaping; Li, Xiaofang
Abstract : Zn-air battery, like other electrochemical power devices such as fuel cells, has the advantages of environmental friendliness and high energy convert efficiency. One of the main problems facing Zn-air battery is how to improve the electrocatalytic activity of the cathode catalyst with low cost and simple preparation process. Herein, N-doped carbon nanosheets/nanotubes composite loaded Fe-Co nanoparticles were prepared via a facile pyrolysis of the solid mixture composed of dicyandiamide, sucrose, cobalt nitrate, iron nitrate, iron phthalocyanine (FePc) and cobalt phthalocyanine (CoPc). The samples were well characterized and their electroactivity towards oxygen reduction reaction (ORR) was tested in a full pH range including acidic, neutral and alkaline media. In 0.1 mol l −1 KOH solution, the ORR onset potential and half-wave potential of the FeCo-FePc/NTu-CNsh are 1.03 V and 0.91 V, which are very close to the performance of commercial Pt/C catalyst (40%). In neutral solution (1 M KCl+4 M NH4 Cl), FeCo-FePc/NTu-CNsh presents an ORR onset potential of 0.93 V and half-wave potential of 0.82 V, which are superior to Pt/C with onset potential of 0.92 V and half-wave potential of 0.81 V. The home-made Zn-air battery with the prepared samples as the cathodic catalysts reveal excellent performance, and the FeCo-FePc/NTu-CNsh Zn-air battery presents a maximum power density of 281.8 mW·cm −2 as well as the high stability at different discharging current densities.